41. Migration as a Woman’s Right: Stories from Comparative and Transnational Slavery Histories in the North Atlantic and Indian Ocean Worlds - SenGupta, Gunja (Open Book Publishers, 2019)
Transnational perspectives on slavery have yielded the important insight that migration makes meaning; that civic identities transform in transit from one place to another. During the nineteenth century, the march of abolition and empire balkanized and realigned the Atlantic and Indian Ocean worlds along political, philosophical, and jurisdictional boundaries of difference over slavery. An imperial behemoth loomed over these divisions on the high seas and the lands that bordered them. For tha.